Surfactant directed synthesis of calcium aluminum layered double hydroxides nanoplatelets - Wongariyakawee, A; Schaeeffel, F; Warner, J; O'Hare, D (2012)
The controlled nucleation and growth of dispersed nanosized calcium, aluminum layered double hydroxide [Ca 2Al(OH) 6DDS] ·H 2O (CaAl-DDS) in dodecylsulfate (DDS) derived reverse micelles has been investigated. Five different inverse micelle compositions were studied, with water:DDS (w) = 10, 20, 30, 40, and 50. These conditions were used to prepare the LDHs denoted as CaAl-DDS RMn (n = 10, 20, 30, 40 and 50). The size of the CaAl-DDS nanosheets can be controlled by the w ratio which results in the synthesis of uniform CaAl-DDS nanoplatelets ranging from 18 nm to 100 nm. AFM measurements show that CaAl-DDS nanoplatelets samples prepared in DDS derived reverse micelles with a w ratio of 50 have thickness of ca. 5 nm which correspond to 2 stacking repeats. © 2012 The Royal Society of Chemistry.